Proportion of Maternal Near-Miss and Its Determinants among Northwest Ethiopian Women: A Cross-Sectional Study - Asaye, Mengstu Melkamu (International Journal of Reproductive Medicine, 2020)
Background. Life-threatening situations might arise unexpectedly during pregnancy. Maternal near-miss can be a proxy for maternal death and explained as women who nearly died due to obstetric-related complications. It is recognized as the predictor of level of care and maternal death. Maternal near-miss evaluates life-threatening pregnancy-related complications, and it directs the assessment of the quality of obstetric care. Objective. To determine the proportion and factors associated with maternal near-miss at maternity wards at the University of Gondar Referral Hospital, Northwest Ethiopia, 2019. Methods. A cross-sectional study design was carried out from March 1 to June 20, 2019, using WHO criteria for maternal near-miss at the University of Gondar Referral Hospital. The data are from the interviews and review of 303 systematically selected participants’ medical files at maternity wards. Bivariate and multivariable logistic regression analyses were performed to analyze factors associated with maternal near-miss, including estimation of crude and adjusted odds ratios and their respective 95% confidence intervals and p value less than 0.05 through SPSS version 20. Result. The study revealed that the proportion of maternal near-miss was found to be 15.8% (95%CI=11.9%-20.1%). In the adjusted analyses, maternal near-miss was significantly associated with low (≤1000 ETB) monthly income (AOR=399; 95%CI=1.65, 9.65), seven or more days of hospital stay (AOR=5.43; 95%CI=2.49, 11.83), vaginal bleeding (AOR=2.75, 95%CI=1.17, 6.47), and pregnancy-induced hypertension (AOR=5.13; 95%CI=2.08, 12.6). Conclusion and Recommendation. The near-miss proportion was comparable to that in the region. Associated factors were low monthly income, seven or more days of hospital stay, vaginal bleeding, and pregnancy-induced hypertension. Thus, giving attention on early identification and treatment of these potential factors can be the opportunity in the reduction of maternal morbidity and mortality.